Functions of the E-class Floral Homeotic Genes in Several Common Dicotyledons - Pu, Zuo-Qian; Xu, Zi-Qin (Journal of plant growth regulation, 2022)
The identity of the floral organs is defined by a small group of transcriptional regulators, and the activities of these proteins can specify the feature of the different whorls in flowers. In the last thirty years, formation of the floral organs remained as the main research subject in plant, especially in Arabidopsis thaliana . By using A. thaliana as material, relevant research works have established a basic architecture for the development of floral organs in higher plants, and it was named as the ABCDE model. In accordance with this model, the identity of the different floral organs can be confirmed by the specific combinations of A-, B-, C-, D-, or E-class floral homeotic genes. SEP -like genes encode MADS transcription factors required for the development of all the four whorls of floral organs and for the determinacy of the floral meristems. In ABCDE model, these genes are defined as E-class floral homeotic genes. A great deal of studies have shown that the proteins encoding by these genes are the main regulators of flower development and act pivotal parts not only in organ identification but also in organ morphogenesis. In this paper, the functions of the E-class floral homeotic genes in dicotyledons are reviewed, and the progress that has been made in characterization of the floral organ identity factors in A. thaliana and other dicotyledons is discussed.